Endogenous BTG2 expression stimulates migration of bladder cancer cells and correlates with poor clinical prognosis for bladder cancer patients - Wagener, Nina; Bulkescher, J.; Macher-Göppinger, Stephan; Karapanagiotou-Schenkel, Irini; Hatiboglu, Gencay; Abdel-Rahim, M.; Abol- Enein, H.; Ghoneim, M. A.; Bastian, P. J.; Müller, S. C.; Haferkamp, A.; Hohenfellner, Markus; et al. (British journal of cancer, 2013)
The B-cell translocation gene 2 (BTG2) is considered to act as a tumour-suppressor gene because of its antiproliferative and antimigratory activities. Higher levels of BTG2 expression in tumour cells have been linked to a better clinical outcome for several cancer entities. Here, we investigated the expression and function of BTG2 in bladder cancer.